2016
DOI: 10.1007/s11136-016-1311-9
|View full text |Cite
|
Sign up to set email alerts
|

The health-related quality of life of Indigenous populations: a global systematic review

Abstract: Ensuring that the HRQoL of Indigenous populations is being appropriately measured is vital to prioritising available resources to the most effective interventions. HRQoL instruments present an opportunity to directly elicit and incorporate Indigenous preferences and conceptions of health into these decisions. Further work is required in the field to ensure that this potential is realised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 53 publications
0
71
0
1
Order By: Relevance
“…Two recent comprehensive reviews revealed significant shortcomings in the availability of appropriate psychometric assessments of wellbeing or quality of life for Indigenous people and identified a clear need to develop new indicators and assessments designed specifically with and for this population [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Two recent comprehensive reviews revealed significant shortcomings in the availability of appropriate psychometric assessments of wellbeing or quality of life for Indigenous people and identified a clear need to develop new indicators and assessments designed specifically with and for this population [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…CHU-9D is a validated generic multi-attribute utility instrument for children 7 years and older; however, its validity in measuring oral health specific utility is a contentious issue [17,24]. Using a Western-type quality-of-life instrument to assess Indigenous populations may not capture the correct information [25]. Also, there are valid arguments as to whether CHU-9D is capable of capturing quality-of-life issues in this unique culture [26].…”
Section: Discussionmentioning
confidence: 99%
“…An economic evaluation will be conducted as part of this study. Best-practice methods will be utilised to undertake a cost-utility analysis of the intervention with quality of life as measured and valued by the EQ-5D as the primary outcome measure [44]. Resource use associated with the development and implementation of the Let's CHAT model of care (including staff time spent developing and administering the program, consumables, software development and others) will be carefully documented, measured and valued.…”
Section: Health Economic Analysismentioning
confidence: 99%